BEHAVIORAL DECISION STYLE AMONG THE COLLEGE PRINCIPALS IN KANYAKUMARI DISTRICT, TAMILNADU - Subathra, C. (International Journal of Research -GRANTHAALAYAH, 2016)
Decision-making is one of the most important elements in the administration of any organization. In higher education, college is an institution, in which the principal is a prime person who makes decision. This article investigates the perception of college principal towards his decision Making style. Numerous studies in the area of Management and Leadership indicate that one’s decision making style (DMS) is reflective of one’s leadership style. Using the Decision Making Styles Inventory (DMSI) developed by Rowe and Boulgarides (1992), this paper attempts to explore and report the managerial DMS among 130 college principals in Kanyakumari District. The scores derived from Decision making inventory were categorized into four decision styles namely: Directive, Behavioral, Analytical and Conceptual. Results revealed that a majority of principals adopted a very dominant or dominant intensity level for Behavioral Decision Making Style.